Flaps vs. Wet Dressings for Fingertip Injuries in Occupational Patients (London Journal of Medical and Health Research, 2025)
Fingertip injuries are common injuries in hand pathology and sometimes extremely disabling (1). The main objective of treatment is to achieve a functional and cosmetic result with adequate thickness of the pulp, digital length (2,3,4), recovering distal sensitivity and function, with a prompt return to the work environment. Depending on the type of injury, several options are available in the literature (5). When reimplantation is not possible due to anatomical or logistical reasons, local or regional flaps are a useful alternative to obtain early coverage (4). In this work we contemplate the use of wet dressings (semi-occlusive bandage) as a definitive treatment for finger injuries with or without bone exposure, since we achieve optimal results in the short term (6 months) with this method. The objective of this work is to compare the results obtained in the treatment of these injuries with the methods used in our environment.
Keywords: urogenital abnormality; anorectal malformation